2020
DOI: 10.1088/1361-6641/ab7434
|View full text |Cite
|
Sign up to set email alerts
|

Improved photodetector performance of SnO2 nanowire by optimized air annealing

Abstract: This study demonstrates the fabrication of uniform and vertically oriented SnO 2 nanowires (NWs) using glancing angle deposition technique. The SnO 2 NW was then subjected to different annealing temperatures of 350 °C, 550 °C, 650 °C, 750 °C and 900 °C in air, each for 1 h to discover the best optimized photodetector performance. The 650 °C sample showed the best photodetector material properties, with highest optical absorption, crystallinity, and reduced dislocation density. As such, the photodetector based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The SnO 2 belongs to a class of materials that combine low electrical resistance with high optical transparency and its conductivity is generally attributed to nonstoichiometry associated with oxygen vacancies in the SnO 2 lattice [6]. In addition to SnO 2 , a wide variety of SMO, such as Ga 2 O 3 [11], ZnO [12], ITO [13], CeO 2 [14], exhibit potential for optoelectronic applications, but SnO 2 is one of the most widely used materials because of its high optical, electrical and chemical stability and its high quantum efficiency in the ultraviolet (UV) region [6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The SnO 2 belongs to a class of materials that combine low electrical resistance with high optical transparency and its conductivity is generally attributed to nonstoichiometry associated with oxygen vacancies in the SnO 2 lattice [6]. In addition to SnO 2 , a wide variety of SMO, such as Ga 2 O 3 [11], ZnO [12], ITO [13], CeO 2 [14], exhibit potential for optoelectronic applications, but SnO 2 is one of the most widely used materials because of its high optical, electrical and chemical stability and its high quantum efficiency in the ultraviolet (UV) region [6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This performance is significantly better than reported metal oxide-based selfpowered photodetectors. [35][36][37][38] What's more, the performance of the detector is comparable to that of 2D material metal sulfide or perovskite based self-powered photodetectors. [39][40][41][42] Therefore, our detector has great application value because of its low-cost and straightforward experimental method and large scale film with high quality.…”
Section: Photoresponse Characteristics Of the Sno 2 Nano Litchi Shell Structure/n-si Heterojunction Photodetectormentioning
confidence: 92%
“…It is observed that the annealed 400 °C sample shows least micro-strain and dislocation density as compared to as-deposited and all others annealed samples. This signified that the 400 °C annealed sample has minimum numbers of defect density as compared to all the other samples [18,19]. Beyond 400 °C temperature the defect density increases which is due to the creation of new monocrystalline peaks forming non-stoichiometric ZnO films at higher annealed temperature.…”
Section: Morphological Structural and Optical Analysis Of Zno/cuo Axi...mentioning
confidence: 93%
“…where, k is the shape factor of 0.94, λ is the wavelength of x-ray, β is full-width-half maxima in radian, θ is the diffraction angle in radian, D is the crystallite size and n is equal to 1. On calculation, it is observed that D gradually increases on annealing which signifies that the crystal structure is improved and full-width-at-half-maximum (FWHM) is decreased [5,18] as shown in table 1. Figures 2(a) and (b) shows bar graph representation of micro-strain (ε) and dislocation density (δ) of all the fabricated samples (as-deposited and annealed samples).…”
Section: Morphological Structural and Optical Analysis Of Zno/cuo Axi...mentioning
confidence: 96%
See 1 more Smart Citation